How to do 187th question?

enter image source here enter image source here

2 Answers
Mar 30, 2018

See below.

Explanation:

Considering the rope length LL and calling

y_1 = m_1 y1=m1 coordinate
y_2 = m_2 y2=m2 coordinate
y_c = yc= pulley center coordinate

We have

y_c-y_1+y_c-y_2=Lycy1+ycy2=L or

2y_c=y_1+y_2+L2yc=y1+y2+L

now deriving twice

2 ddot y_c = ddot y_1 + ddot y_2

but ddot y_c = a_0, ddot y_1 = a_1, ddot y_2 = a_2

{(T-m_1(a_0+g)=m_1a_1),(T-m_2(a_0+g)=m_2a_2),(2a_0=a_1+a_2):}

Solving those equations we obtain

{(T = 2(2a_0+g)(m_1m_2)/(m_1+m_2)),(a_1 = 3 a_0 + g - (2 (2 a_0 + g) m_1)/(m_1 + m_2)),(a_2=((3 a_0 + g) m_1 - (a_0 + g) m_2)/(m_1 + m_2)):}

we leave the conclusions to the reader.

Mar 31, 2018

The question asks for each one is Incorrect...
(4)

Explanation:

As general statement:
-a_1=a_0=a_2

Since m_1 is heavier it till go down by some -a_1, now that value has to have the same magnitude as a_2 because that is the acceleration m_2 upwards and as shown by the picture that is equal to a_0

Here's the formula for tension of two masses:
T= m_2g+m_2a_0
T= m_1g-m_1a_0

Substitute for a_0:
T= m_2g+m_2a_2
Number 2 is correct

Substitute for a_0:
T= m_1g-m_1(-a_1)
T= m_1g+m_1a_1
Number 1 is also correct

Number 3 however refers to the MAGNITUDE of relative acceleration in comparison to the pulley, so we can add to our statement: -a_1=a_0=a_2= a_r
Substitute for a_0:
T= m_1g-m_1(a_r)
T= m_1g-m_1a_r
T= m_1(g-a_r)
Number 3 is also correct

Number 4 is incorrect because:
going back to:
T= m_2g+m_2a_0
T= m_1g-m_1a_0

Solve for a_0 in both and set them equal:
a_0= (T-m_2g)/m_2
a_0= (T-m_1g)/-m_1

So:
(T-m_2g)/m_2= (T-m_1g)/-m_1

(-m_1T+m_2m_1g)/m_2= (T-m_1g)

-m_1T+m_2m_1g= m_2T-m_1m_2g

m_2m_1g+m_1m_2g= m_2T+m_1T

m_2m_1g+m_1m_2g= T(m_2+m_1)

(2m_1m_2g)/(m_2+m_1)= T